Mapping Sustainable Marketing Using Bibliometric Analysis - F Fitria; Desi Tia Adisti; D Dea; Agum Gumelar; Adi Setiawan (Apollo: Journal of Tourism and Business, 2024)
Research on sustainable marketing is mapped using bibliometric analysis, which offers a thorough picture of the field's current condition and future directions. By means of bibliometric analysis using VosViewer and the collection of 1.385 articles, the study indicates a noteworthy increase in publications and citations concerning the subject matter during the last ten years. Several important clusters actively studying Sustainable Marketing, including sustainable consumer behavior, sustainability orientation, consumption patterns, market segmentation, and stakeholder roles, were found through analysis of author collaboration patterns. "Sustainable marketing research" is the core research area, and the bibliometric network visualization displays the essential terms and relationships between concepts. Though less thoroughly, subjects including customer capital, sustainable management, sustainable business, and digital marketing were also covered. This article's bibliometric analysis reveals some intriguing mapping findings. Collaboration in research articles is revealed by the author's analysis. The report also presents the findings from studies on sustainable consumer behavior. The study method on consumer sustainability challenges, including customer capital, spending, and behavior, is outlined by the bibliometric analysis. Bibliometric analysis, thus, offers a mapping of sustainability research, particularly in terms of offering significant insights on specific sustainability challenges like consumer difficulties.